Singing Language : Integrating Second Language Learning into Choir Practice - Lehtinen-Schnabel, Johanna; Levänen, Sari (Sage, 2024)
Language and music are closely tied in singing. It has even been argued that without language there is no song. However, can music and language learning through singing also be seen as being closely tied without first highlighting the boundaries between these disciplines? This study emphasizes a nonhierarchical approach to music and language learning by intertwining musical and linguistic activities in a choir context. The study explores the extent to which singing in a language-responsive choir can encourage productive second language use and enhance the sound hearing, phonological processing, pronunciation, and spoken language skills of adult choir participants with culturally and linguistically diverse backgrounds. The research material consists of individual pre-, middle-, and post-interviews and Phonology pre- and post-tests that were conducted with volunteer choir participants during 2019–2020. The analysis encompasses both thematic and statistical approaches. The findings are reflected through a hybrid choir practice that draws on a three-way dialogue between choir participants, the choir conductor, and the second language teacher. The results suggest that active and holistic second language use in a language-aware choir context decreases phonological challenges in second language auditory processing and verbal production, including spoken language. The findings of the interviews and the Phonology tests were in line with each other.
Keywords: oppiminen; toinen kieli; kielen oppiminen; englannin kieli; musiikki; opetus; ääntäminen; kuorot